Análise cênica e diversidade visual de paisagens:: contribuições para a gestão das trilhas turísticas no Parque Nacional da Chapada dos Veadeiros - GO - Gomes Pereira Silva, Romero; Henke-Oliveira, Carlos; Hiroo Saito, Carlos (Sustainability in Debate, 2013)
Scenic analysis and landscape visual diversity: contributions to tourist tracks management in the Parque Nacional Chapada dos Veadeiros. The analysis of landscape scenic quality based on geotechnology reduces the subjectivity problem in visual impact assessments for tourism tracks planning. Employing the viewshed technique we conduced an analysis of landscape quality and diversity for active tracks on Parque Nacional da Chapada dos Veadeiros (Goiás, Brazil), aiming to identifying alternatives for tourism management. The track called “Trilha dos Saltos” shows the greater performance in terms of viewshed size and its scenic quality. The intersection of viewsheds for the two main tracks covers 20.13 km², representing sites that request specific researches to supply subsidies towards the implementation a landscape management policy. The applied technique minimizes the effects of negative environmental impacts, allows an analysis of the best options for visitation purposes and identifies priority areas for environmental management towards the sustainable tourism.